(untitled) (Aporte Santiaguino, 2024)
This paper compiles various research on the influence of concrete with polypropylene fiber additives (FPP). An exploratory-descriptive-quantitative methodology is employed, without direct intervention in the research process. The sample includes 26 relevant studies conducted at local, national, and international levels, focusing on rigid pavements. Local studies highlight improvements in f’c and MR with the addition of FPP, although excessive doses may reduce these properties. The optimal dosage of FPP is typically around 6% relative to the weight of cement. Nationally, research is conducted on cracking, strength, and workability of concrete, varying FPP dosages and evaluation methods. Internationally, tensile strength, durability, and concrete performance are examined, with emphasis on resistance to abrasion and temperature. The results show improvements in strength and durability with the addition of FPP, although the optimal dosage and effects on concrete properties vary depending on the specific conditions of each study. It was determined that concrete reinforced with FPP can significantly enhance the properties and durability of rigid pavement. This has a favorable outcome on the f’c, flexural strength, and fatigue of the pavement, as well as its ability to resist cracking and abrasion.